Institutional Features of the Development of Competitive Cryptocurrency - V. P. Bauer; V. V. Smirnov (Финансы: теория и практика)
The aim of the article is to clarify the basics of the digitalization strategy of the competitive businesses and identify features of the institutional environment that ensure the development of cryptocurrency as a new asset (IT product) of the modern economy, analyze the methods of implementing the cryptocurrency business models. The relevance of the research paper is determined by the need to develop a competitive Russian cryptocurrency (including the cryptoruble) with the growing private, state and cross-national cryptocurrencies. The scientific novelty of the study implies clarifying the informal and formal rules of the institutional environment and related methods ensuring the development of a competitive cryptocurrency. The authors consider the following methods to implement the institutional features of  the  cryptocurrencies  business  model  development:  logic  and  blockchain  algorithm  that  establish  trust  and  collaboration between cryptocurrency developers; logic and blockchain consensus algorithm ensuring  that  all  the parties of the blockchain network come to a common agreement (consensus); logic and blockchain algorithms that form cryptocurrency transactions and control its turnover by generating blocks of cryptocurrencies, by forming the structure of blocks and transactions of cryptocurrencies, by storing cryptocurrencies’ keys and providing security, by mining (forging) cryptocurrency, etс.The results of the study provide a basis for identifying the institutional features and the corresponding methods providing a competitive cryptocurrency development with a detailed analysis of the blockchain consensus algorithms that ensure the competitiveness of the cryptocurrency. The conclusions show that the most promising are the hybrid consensus algorithms which may include both the logic of two or more known algorithms and the original logic of a new algorithm. The authors recommend defining the logic of the blockchain consensus algorithm as a priority when developing a cryptocurrency to ensure reliability of the transactions in the blockchain network, thus increasing the competitiveness of the cryptocurrency.